Wernicke encephalopathy with atypical imaging findings in a depressed patient: A case report - Hiroyuki Tokue; Rei Ishikawa; Kiyohiro Oshima; Yusuke Sawada; Yuto Aramaki; Kei Kawano; Takumi Nihei; Kouta Isogai; Kohei Kawahara; Takayuki Yokota; Hiroyuki Yasui; Miho Ikeya; et al. (Radiology Case Reports, 2024)
This case report highlights the rare occurrence of Wernicke encephalopathy caused by malnutrition in a depressed patient with atypical imaging findings. A 60-year-old female with depression developed a disturbance of consciousness owing to Wernicke encephalopathy. Magnetic resonance imaging showed abnormal signals in the thalamus and mammillary bodies around the third ventricle, cerebral aqueduct, and fourth ventricle. Abnormal signals were also present in the cerebral cortex around the central sulcus, and an intracranial hemorrhage from the thalamus was observed. Therefore, clinicians should consider Wernicke encephalopathy in the differential diagnosis of altered consciousness in depressed patients. Early assessment of nutritional status and prompt intervention are crucial in cases of prolonged depression-related malnutrition.